АКСІОЛОГІЧНІ ЗАСАДИ ОСВІТОЛОГІЇ: ДЕРЖАВА, СУСПІЛЬСТВО І ОСОБИСТІСТЬ - Khoruzha, L (Continuing Professional Education: Theory and Practice, 2019)
The article studies the value basis of the interaction between the state, society and individual as for the development of education in the context of the new scientifi c notion named as «osvitologiуa». The common scientifi c fi eld of the three main subjects of the development of education makes this process more effective.